Romans Teodora Prodromosa Przygody Rodante i Dosyklesa (księga pierwsza). - Cyrulski, Marcin (Scripta Classica, 2019)
In the twelfth century, in Constantinople, in the Komnenian epoch, four novels were written. After eight centuries, the old Greek literary genre appeared in Byzantium. One of these novels was Rodante and Dosikles by Theodore Prodromos. This Byzantine romance concernig the adventures of Dosikles and his beloved Rodante has been already translated into Latin, French, German, Italian, Spanish, Serbian and recently English. In Scripta Classica the Polish translation of the first book of Rodante and Dosikles is published (although Prodromos' novel consists of nine books).